Caracterização silvicultural, botânica e avaliação da variabilidade genética por meio do marcador molecular RAPD em um teste de progênies de Eucalyptus urophylla S. T. Blake - Pigato, Silvana Maria Paes Cangiani [UNESP]; Lopes, Catalina Romero [UNESP] (My University, 2001)
Molecular markers have recently been incorporated into genetic improvement programs. They are already considered as powerful tools with several different uses, for instance the monitoring of genetic variability in tree populations. The main objectives of this study were to evaluate genetic variability in Eucalyptus urophylla progenies and together with silvicultural and botanical information, provide assistance to the improvement program. The Eucalypts population is located at the Experimental Forestry Sciences Station, Anhembi, SP, which belongs to the College of Agriculture Luiz de Queiroz. Sixty-nine progenies were analysed representing one individual by family in open pollinated Eucalyptus urophylla trees. The RAPD technique allowed the identification of 72 loci that were analysed using Jaccard's Coefficient generating a genetic similarity matrix to permit estimation of genetic distances. The results obtained showed genetic distance between individuals of 0.40 with 12 groups of genetic variability using a standardised distance of 40%. The progenies showed different bark patterns, allowing the establishment of bark groups. The groups formed based on genetic distances obtained using DNA analysis did not correspond to those based on bark pattern. Genetic selection was simulated in which silvicultural and genetic variability data were linked, thus avoiding excessive variability losses. The simulation of controlled crossings allowed the maximum genetic difference to be obtained linked with height and individual bark roughness.
Silvicultural and botanical characterization and genetic variability by RAPD molecular marker in progeny trial of Eucalyptus urophylla S. T. Blake
Keywords: Botanical characterization; Eucalyptus urophylla; Molecular genetic; Molecular marker; Silvicultural characterization